CHILD-MOTHER COMMUNICATION STYLE REVIEWED FROM THE MOTHER'S EMPLOYMENT STATUS - Kiki Savitri (Universitas Negeri Semarang, 2026)
The role of mothers in the family is very important in shaping the emotional and spiritual intelligence of children, which affects their moral, intellectual, psychological, and social development. Working mothers, especially factory workers, often face time constraints with their children that can diminish emotional attachment and affect cognitive and social development. However, effective communication and quality time can mitigate these negative impacts. The research uses a mixed methods approach with the population being working mothers who have children in TK Ananda 2 Kalongan and TK Harapan Kalirejo. The total population is 97 mothers at TK Ananda 2 Kalongan and 76 mothers at TK Harapan Kalirejo, with 40 respondents from each class. A sample of 40 was determined for each kindergarten. The results show a value of α < 0.05, indicating a significant difference between the communication styles of housewives and factory workers. The research findings on housewives indicated they used open assertive communication and allowed for discussion, while factory workers tended to use non-assertive communication due to limitations in time and energy